ChemInform Abstract: p‐Nitrophenyl Ethylthioester in Enantioselective Organocatalytic Michael Additions: Different Behavior of β‐Aryl and β‐Alkyl Enals. Issue 13 (1st April 2014) - Duce, Sara; Jorge, Maria; Alonso, Ines; Garcia Ruano, Jose Luis; Cid, M. Belen
Abstract The differences in the reactivity of the thioesters (I) with β‐alkyl and β‐aryl‐substituted enals (II) are overcome by optimization allowing the synthesis of diastereomeric mixtures of Michael adducts (III) and (IV).